Ability of 3 extraction methods (BCR, Tessier and protease K) to estimate bioavailable metals in sediments from Huelva estuary (Southwestern Spain) - Rosado Alcarría, D. (2016)
The bioavailable fraction of metals (Zn, Cu, Cd, Mn, Pb, Ni, Fe, and Cr) in sediments of the Huelva estuary and its littoral of influence has been estimated carrying out the most popular methods of sequential extraction (BCR and Tessier) and a biomimetic approach (protease K extraction). Results were compared to enrichment factors found in Arenicola marina. The linear correlation coefficients (R2) obtained between the fraction mobilized by the first step of the BCR sequential extraction, by the sum of the first and second steps of the Tessier sequential extraction, and by protease K, and enrichment factors in A. marina, are at their highest for protease K extraction (0.709), followed by BCR first step (0.507) and the sum of the first and second steps of Tessier (0.465). This observation suggests that protease K represents the bioavailable fraction more reliably than traditional methods (BCR and Tessier), which have a similar ability. © 2015 Elsevier Ltd.